Bridging Local Wisdom and Islamic Character Education: Madrasah Teachers’ Perspectives on Sintuwu Maroso as a Pedagogical Framework - Ahmad Nasir; Sawal Sawal; Sakinah Aljufri; Wandy Renaldy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The growing need for contextual and culturally responsive character education has increased scholarly interest in the integration of local wisdom within Islamic educational settings. One form of local wisdom with significant educational potential is Sintuwu Maroso, a cultural philosophy of the Poso community that emphasizes solidarity, togetherness, mutual respect, and collective responsibility. This study aimed to explore how madrasah teachers interpret the values embedded in Sintuwu Maroso and examine its relevance as a pedagogical foundation for Islamic character education. The study employed a qualitative approach using an interpretive case study design. Data were collected through semi-structured interviews, field notes, and document analysis involving 30 madrasah teachers in Poso Regency, Central Sulawesi, Indonesia. The data were analyzed using thematic analysis. The findings revealed four major themes: Sintuwu Maroso as a foundation for social cohesion, its compatibility with Islamic character values, its pedagogical integration within madrasah education, and the challenges and opportunities associated with local wisdom-based character education. The findings indicate that teachers perceive Sintuwu Maroso as a culturally grounded value system that aligns closely with Islamic principles such as ukhuwah (brotherhood), ta’awun (mutual assistance), social justice, and moral responsibility. Furthermore, these values are integrated into educational practices through collaborative learning, teacher role modeling, and contextual social activities. This study contributes to the development of culturally responsive Islamic education by positioning local wisdom as a pedagogical framework that connects religious teachings, cultural experiences, and character formation. The findings also highlight the importance of integrating local cultural values into character education programs in multicultural educational contexts.